Is a therapeutic anticoagulation window needed for delivery when using prophylactic low molecular weight heparin during pregnancy? A retrospective monocentric study. (August 2017) - Roueli, Assila; Cesario, Elsa; Amsellem, Julien; Agman, Antoine; Vauthier-Brouzes, Danièle; Nizard, Jacky
Abstract: Objectives: The aim of the study was to evaluate the usefulness of therapeutic window for delivery for patients under prophylactic anticoagulation by low molecular weight heparin (LMWH) by comparing those who had a planned delivery versus those who delivered spontaneously. Study design: This retrospective monocentric study included pregnant patients with prophylactic anticoagulation (one injection per day of enoxaparin 4000 UI), who delivered after 24 weeks of gestation. We collected data on pregnancy characteristics and on the delivery. We divided patients in two groups: GROUP S were patients who delivered spontaneously and GROUP P were patients who had a planned delivery for a therapeutic anticoagulant window. Our primary endpoint was the neuraxial anaesthesia rate. We compared the two groups with the student test for quantitative data and the Chi-2 test or the exact test of Fisher for qualitative data. Results: Over a 3.5 years period, we included 100 pregnant patients with prophylactic anticoagulation. Indications of prophylactic LMWH were patients with a low risk of thrombosis, mostly personal history of cured deep venous thrombosis (36%) prior to pregnancy or non-thrombotic antiphospholid syndrome (37%). The overall rate of neuraxial anaesthesia during delivery was 86%. Twenty-six patients were included in GROUP S and 74 in GROUP P. In GROUP P, all patients had access to neuraxial anaesthesia versus 88.4% (23/26) in the GROUP S (p < 0.0001). For the three remaining patients, the contraindication was a short delay between the last injection of LMWH and the need for anaesthesia. The mean delay between the last injection of LMWH and neuraxial anaesthesia was 42.6 +/− 24.1 (13–123) h in the GROUP P and 22.7 +/− 9.9 (11–42) h in the GROUP S (p < 0.0001). One patient had deep venous thrombosis in the 6 weeks postpartum, in the GROUP P. Conclusion: With a planned induced delivery between 38 and 39 weeks of gestation, 11.5% of patients who went into spontaneous labour before induction would not have a neuraxial anaesthesia when respecting the 12 h delay between the last injection of low molecular weight heparin and the need for anaesthesia.